Adherence to a Gluten-free Diet: Assessment by Dietician Interview and Serology. Issue 3 (March 2018) - Mehta, Pooja; Pan, Zhaoxing; Riley, Marisa D.; Liu, Edwin
Abstract : ABSTRACT: We aimed to determine whether tissue transglutaminase (tTG) autoantibody positivity was associated with dietitian-assessed adherence to a gluten-free diet in pediatric patients with celiac disease and identify areas where adherence falters. We reviewed the records of children with celiac disease who had a standardized evaluation of adherence by a registered dietitian. A negative tTG value was not associated with good adherence ( P  = NS). Adherent and nonadherent children differed with respect to purposeful and accidental gluten exposure ( P  < 0.0001), knowledge ( P  = 0.003), cross-contact ( P  = 0.003), potential exposure via medications and cosmetics ( P  = 0.004), and potential exposure while at restaurants ( P  < 0.0001), but not with respect to potential exposure at school ( P  = NS). Based on our findings, we suggest that negative tTG levels are not necessarily indicative of good adherence to a gluten-free diet in pediatric patients with celiac disease. A separate assessment of adherence is needed focusing on knowledge, behavior while dining out, and intent to adhere. Abstract : Supplemental Digital Content is available in the text